GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 483 species occurrences available in GBIF matching the query: TaxonKey: Ursus americanus subsp. americanus. The dataset includes 483 records from 20 constituent datasets: 5 records from SUI Vertebrate Collection. 11 records from KUBI Mammalogy Collection. 180 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 9 records from Cowan Tetrapod Collection - Mammals. 20 records from Field Museum of Natural History (Zoology) Mammal Collection. 6 records from CHAS Mammalogy Collection (Arctos). 94 records from Museum of Comparative Zoology, Harvard University. 33 records from iNaturalist Research-grade Observations. 2 records from DMNS Mammal Collection (Arctos). 3 records from CAS Mammalogy (MAM). 28 records from UMMZ Mammal Collection. 1 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 12 records from LACM Vertebrate Collection. 15 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 2 records from TTU Mammals Collection. 9 records from UCLA Donald R. Dickey Bird and Mammal Collection. 4 records from UCM Mammal Collection (Arctos). 41 records from AMNH Mammal Collections. 1 records from MSB Mammal Collection (Arctos). 7 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences